Self-Healing Natural Rubber- Preparation And Characterization - Loh, Leh Hee (Universiti Sains Malaysia, 2017)
The objective of this research was to develop a new self-healing natural rubber with the motivation to introduce self-healing capability using conventional rubber processing equipment and ingredients. The research’s stage 1 investigated the intrinsic self-healing ability of the natural rubber by modification of vulcanization system. The natural rubber compounds were vulcanized with different types of vulcanization system at different curing time. The results showed that the rubber compound with semi-efficient (Semi-EV) vulcanization system have the higher healing efficiency of tensile strength and elongation at break. However, the healing efficiency decreased as the curing time increased from t30, t50 to t70. Research’s stage 2 investigated the self-healing capability of a natural rubber by using binary vulcanization agents. It was found that the healing efficiency of tensile strength and elongation at break for rubber compounds vulcanized with sulfur/Si 69 is generally higher than those vulcanized with sulfur/DCP and DCP/Si 69. Evidence from scanning electron microscopy (SEM) supported that the healed samples vulcanized using sulfur/Si 69 showed no obvious gap between the healed crack surfaces.